Multi-Scale Characterisation and Mechanical Adhesion in PVD-Deposited Ca-SZ Coating for Implantable Medical Devices - Alex Tchinda; Richard Kouitat-Ndjiwa; Pierre Bravetti (Biomedicines)
Oral implantology faces a multitude of technical challenges in light of current clinical experience, underlining the need for innovation in implantable medical devices in both mechanical and biological terms. Objectives: This study explores the influence of the thickness factor of calcium-doped zirconia (Ca-SZ) coatings deposited by PVD on their intrinsic mechanical properties and the determinism of the latter on adhesion to the TA6V alloy substrate after mechanical loading for applications in dental implantology. Methods: Three separate thicknesses of 250 nm, 450 nm and 850 nm were evaluated in terms of mechanical strength, modulus of elasticity and adhesion to the substrate, in accordance with ISO 20502:2005. Results: The results show an increase in apparent modulus of elasticity with thickness, reaching values of around 25.05 GPa and 36.3 GPa, close to the cortical bone for the 250 nm and 450 nm thick coatings, respectively. Adhesion tests show a progressive improvement up to 450 nm, followed by a similar observation at 850 nm, underlining the importance of optimal thickness to balance mechanical protection and biomechanical compatibility. Furthermore, the initial roughness and topography of the substrate were not influenced by the different thicknesses of the Ca-SZ coating. Conclusions: Together, these results reinforce the potential of Ca-SZ coatings to minimise stress shielding in dental implants.